2012
DOI: 10.1039/c1py00487e
|View full text |Cite
|
Sign up to set email alerts
|

Bis(phosphinimino)methanide borohydride complexes of the rare-earth elements as initiators for the ring-opening polymerization of trimethylene carbonate: combined experimental and computational investigations

Abstract: Bis(phosphinimino)methanide bisborohydride complexes of lanthanum, yttrium and lutetium, [{CH (PPh 2 NSiMe 3 ) 2 }La(BH 4 ) 2 (THF)] ( 1) and [{CH(PPh 2 NSiMe 3 ) 2 }Ln(BH 4 ) 2 ] (Ln ¼ Y (2), Lu (3)), have been investigated in the ring-opening polymerization (ROP) of trimethylene carbonate (TMC). All three initiators afforded linear poly(trimethylene carbonate)s (PTMCs) in toluene at 23 C. 1 H NMR analyses of the polycarbonates revealed the formation of a-hydroxy,u-formate telechelic PTMCs, as previously obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 67 publications
0
26
0
Order By: Relevance
“…Both ligands have been extensively used in main group, 1-16 transition [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and f-element 5,13,15,19,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] chemistry. Both ligands have been extensively used in main group, 1-16 transition [16][17][18][19][20][21][22][23][24][25][26][27][28][29]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both ligands have been extensively used in main group, 1-16 transition [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and f-element 5,13,15,19,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] chemistry. Both ligands have been extensively used in main group, 1-16 transition [16][17][18][19][20][21][22][23][24][25][26][27][28][29]…”
Section: Introductionmentioning
confidence: 99%
“…Calculation studies revealed that the negative charge is mainly localized on the carbene carbon atom of the ligand backbone and that the charge delocalization from carbon to nitrogen is less important. 6,14,16,20,[36][37][38][39][40][41][42][43][44][45][46][47][48][49] In this context, some very efficient rare-earth metal initiators ligated by {CH(PPh 2 NSiMe 3 ) 2 } − have been unveiled for polymerization reactions. Mostly six membered metallacycles (N-P-C-P-N-M) are formed by chelation of the two imine groups to the metal center, adopting a pseudo-boat conformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal alkoxide species, M-OR, have been shown to be the true active species in numerous ROP processes. [1][2][3][4][5][6][7][8][9][10][11][12][13][18][19][20][21][22][23][24] For example, in 2004, Lewiński and co-workers reported the first structurally characterized aluminum ε-caprolactone complex, indicating that the Al-Me group has poor reactivity with CL. 77 Thus, in most ROP cases, an alcohol is used as an initiator and is essential in order to start the polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, based on previous reports, [5][6][7][8][9][10][11][12][13][18][19][20][21][22][23][24][25][26][27] after the insertion of the first equivalent of other monomers (CL, VL, and TMC), the rates of polymerization will not decrease remarkably, indicating that the insertion of the first monomers will not cause such a significant chelation effect like LA. Thus, in these cases, the energy of the initiation step can be used to estimate the energy of propagation.…”
mentioning
confidence: 99%